Altered supraspinal motor networks in survivors of poliomyelitis: A cortico-muscular coherence study. Issue 1 (January 2021) - Coffey, Amina; Bista, Saroj; Fasano, Antonio; Buxo, Teresa; Mitchell, Matthew; Giglia, Eileen Rose; Dukic, Stefan; Fenech, Matthew; Barry, Megan; Wade, Andrew; Heverin, Mark; Muthuraman, Muthuraman; et al.
Highlights: Abnormal coherence patterns provide neurophysiologic evidence of supraspinal change in those affected by poliomyelitis. Cortico-Muscular Coherence changes in Polio patients reflect functional re-organisation of the central-peripheral network. Cortico-Muscular Coherence is a potential biomarker of altered Motor network function in Polio, SMA and other related conditions. Abstract: Objective: Poliomyelitis results in changes to the anterior horn cell. The full extent of cortical network changes in the motor physiology of polio survivors has not been established. Our aim was to investigate how focal degeneration of the lower motor neurons (LMN) in infancy/childhood affects motor network connectivity in adult survivors of polio. Methods: Surface electroencephalography (EEG) and electromyography (EMG) were recorded during an isometric pincer grip task in 25 patients and 11 healthy controls. Spectral signal analysis of cortico-muscular (EEG-EMG) coherence (CMC) was used to identify the cortical regions that are functionally synchronous and connected to the periphery during the pincer grip task. Results: A pattern of CMC was noted in polio survivors that was not present in healthy individuals. Significant CMC in low gamma frequency bands (30–47 Hz) was observed in frontal and parietal regions. Conclusion: These findings imply a differential engagement of cortical networks in polio survivors that extends beyond the motor cortex and suggest a disease-related functional reorganisation of the cortical motor network. Significance: This research has implications for other similar LMN conditions, including spinal muscular atrophy (SMA). CMC has potential in future clinical trials as a biomarker of altered function in motor networks in post-polio syndrome, SMA, and other related conditions.